Lectures on Mappings of Finite Distortion - Hencl, Stanislav; Koskela, Pekka (Lecture Notes in Mathematics, 2014)
In this book we introduce the class of mappings of finite distortion as a generalization of the class of mappings of bounded distortion. Connections with models of nonlinear elasticity are also discussed. We study continuity properties, behavior of our mappings on null sets, topological properties like openness and discreteness, regularity of the potential inverse mappings and many other aspects.